Santo Antônio do Tauá (PA): uma cartografia da expansão urbana - CARMO, Suellen Auzier do (2020)
The present research aimed a cartographic representation of the installation of the street network, indicative of urban expansion and in the Santo Antônio do Tauá City, State of Pará, Brazil. This is a study on the urban formation of a coastal city da Amazonia, under the direct influence of Belém Metropolitan, from documentary sources, to identify the vectors of urban expansion through the elaboration of maps. Thus, proposing a cartographic representation of the rescue of urban expansion, work still unprecedented for this city. The analysis was made using the geoprocessing tools for vectorization, transformation of KML bases for shapefiles, elaboration of maps, showing the expansion of the street network from 1898 to 2018. The maps were produced using the QGIS program version 2.18 “Las Palmas ”. The cartographic bases consisted of old maps, mosaics of images from Google Earth-Pro, topographic maps of the Army (DSG) and field sketches. Using the analysis in this long time interval, it was understood that the city had as its initial vector the lots of Colônia Santa Rosa; it began to expand, effectively, from the 1960s, presenting different phases of expansion in the following decades. From 2000 onwards, the production of peripheral urban spaces through occupations (“invasions”) and residential subdivisions became prominent. Currently, the city expands along the PA-140 highway and surrounding areas connected to it.